BALANCE OF MATTER AND ENERGY FOR DETERMINATION OF THERMAL EFFICIENCY BOILERS - Armijo C., Javier (2006)
We are showing solutions of equations matter and energy conservation steday state for calculate thermal efíiciency of steam generators. The analysis of freedom degree show results are functions of variables chosen as input data. The results indicate chemical reactions contribute with 90 per cent of energy neccesary and expense energy share to steam and exit gas.